Blood NCAPH2 Methylation Is Associated With Hippocampal Volume in Subjective Cognitive Decline With Apolipoprotein E ε4 Non-carriers - Chen, Ying; Li, Tao-Ran; Hao, Shu-Wen; Wang, Xiao-Ni; Cai, Yan-Ning; Han, Ying (Frontiers in Aging Neuroscience, 2021)
Objective: This study assessed the methylation of peripheral NCAPH2 in individuals with subjective cognitive decline (SCD), identified its correlation with the hippocampal volume, and explored whether the correlation is influenced by apolipoprotein E ε4 (APOE ε4) status. Methods: Cognitively normal controls (NCs, n = 56), individuals with SCD (n = 81), and patients with objective cognitive impairment (OCI, n = 51) were included from the Sino Longitudinal Study on Cognitive Decline (NCT03370744). All participants completed neuropsychological assessments, blood tests, and structural MRI. NCAPH2 methylation was compared according to the diagnostic and APOE ε4 status. Partial correlation analysis was conducted to assess the correlations between the hippocampal volume, cognitive tests, and the NCAPH2 methylation levels. Results: Individuals with SCD and patients with OCI showed significantly lower levels of NCAPH2 methylation than NCs, which were independent of the APOE ε4 status. The NCAPH2 methylation levels and the hippocampal volumes were positively correlated in the SCD APOE ε4 non-carriers but not in the OCI group. No association was found between the NCAPH2 methylation levels and the cognitive function. Conclusion: Abnormal changes in blood NCAPH2 methylation were found to occur in SCD, indicating its potential to be used as a useful peripheral biomarker in the early stage of Alzheimer's disease screening.